2016
DOI: 10.21037/atm.2016.05.55
|View full text |Cite
|
Sign up to set email alerts
|

Elevated d-dimer cut-off values for computed tomography pulmonary angiography—d-dimer correlates with location of embolism

Abstract: Background: Acute pulmonary embolism (APE) is a potentially fatal condition, and making a timely diagnosis can be challenging. Computed tomography pulmonary angiography (CTPA) has become the modality of choice, and this contributes to the increasing load on emergency room CT scanners. Our purpose was to investigate whether an elevated d-dimer cut-off could reduce the demand for CTPA while maintaining a high sensitivity and negative predictive value (NPV). Methods:We retrospectively reviewed all patients referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Our findings confirm previous reports regarding the use of age-adjusted Dd cutoff, highlighting that age-adjusted ones increase specificity without increasing false-negative results [ 9 , 21 , 22 , 23 ]. We showed that the absolute percentage of increase in specificity compared with conventional Dd was 5.2%, so the age-adjusted formula is unlikely to significantly decrease the number of patients for whom imaging can be avoided (11% in our study).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings confirm previous reports regarding the use of age-adjusted Dd cutoff, highlighting that age-adjusted ones increase specificity without increasing false-negative results [ 9 , 21 , 22 , 23 ]. We showed that the absolute percentage of increase in specificity compared with conventional Dd was 5.2%, so the age-adjusted formula is unlikely to significantly decrease the number of patients for whom imaging can be avoided (11% in our study).…”
Section: Discussionsupporting
confidence: 92%
“…It must be noted that some patients had normal or not dramatically high D-dimer values even in the presence of severe clinical conditions; in this regard, it may be speculated that the amount of fibrin alteration at the level of tiny subsegmental arterial vessels does not induce the same dramatic changes seen in classic pulmonary embolism (PE), as it is known that a correlation exists between D-dimer values and the location of PEs. 5 As it has already been demonstrated with other viral infections, such as the influenza A virus (IAV), the presence of aggressive inflammation, known as a cytokine storm, is thought to cause most of the damage in the lungs during infection. Similarly, dysfunctional coagulation is a common complication in pathogenic influenza, which manifests through lung endothelial activation, vascular leak, disseminated intravascular coagulation, and pulmonary thrombosis.…”
mentioning
confidence: 99%
“…An article by Kubak et al [ 32 ] was selected as a random example of a correct classification. When provided with the title, abstract, authors, and MeSH terms, as may have been provided at the time of submission, the BERT model correctly predicted that the article would be published in a highest tertile journal ( Annals of Translational Medicine , impact factor of 3.932; Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%